Saberes docentes no ensino superior: compreendendo a aprendizagem profissional a partir da pesquisa (auto)biográfica - Gomes, José Oreste Cirto (2021)
The general objective of this work is to unveil knowledge of teaching in Higher Education, from the mapping of academic productions that dialogue with (auto)biographical narratives. For the composition of the corpus of analysis of this work, we used, as a database, the Revista Brasileira de Pesquisa (Auto)Biográfica (RBPAB). The time frame adopted considers the period from 2016 to 2021, marked by the beginning of the publication of the Brazilian Journal of (Auto)Biographic Research, culminating in the year this research was carried out until the month of November, considering the last published volume (v18). The theoretical framework adopted considers the academic production of different authors who focus their research on teaching knowledge in Higher Education, the construction of identity and teaching professionalism, research through (auto)biographical narratives in Education, among others. For the construction and development of this study, the quantitative-qualitative methodology was chosen, considering the realization of a Systematic Mapping of the academic production inherent to the aforementioned period, as well as the contributions of Falbo, Souza and Felizardo (2017) and Vosgerau and Romanowski (2014), composition of the analysis corpus and production of results. Twenty-six articles published by RBPAB were analyzed. The mapping of academic productions was made from the reading and recording of these works, among which four thematic axes emerged, organized in order to unveil the teaching knowledge in Higher Education, which used (auto)biographical narratives. The academic productions analyzed show that the teachers' memories of their trajectories influenced the generation of important knowledge for their professional training, as the images they had about what it was to be a teacher were related to representations that were being (de)constructed and (re)constructed from self-writing, from reflections on their formative processes, as well as from their professional trajectories and life stories. The narratives about life histories considered as a training device brought us a perspective of the teaching profession as practiced by a human being who needs to be considered as beyond a technically constituted professional, that is, as a person who is, in its entirety. Through this device, the (trans)formation of themselves and their teaching practices occur progressively, while they build and expand their knowledge through their (auto)biographies, as these provide them with opportunities for self-knowledge, self-training and a new way of seeing and living teaching in Higher Education.